Additive manufacturing of eco-friendly building insulation materials by recycling pulp and paper. Issue 9 (17th April 2023) - Lee, Meng-Lun; Sarkar, Arpita; Guo, Zipeng; Zhou, Chi; Armstrong, Jason N.; Ren, Shenqiang
Abstract : Thermal insulation materials by recycling pulp and paper wastes play an important role in environmental sustainability of green buildings. Abstract : Thermal insulation materials by recycling pulp and paper wastes play an important role in environmental sustainability of green buildings. As society is pursuing the goal of zero carbon emissions, it is highly desirable to use eco-friendly materials and manufacturing technologies for building insulation envelopes. Here we report additive manufacturing of flexible and hydrophobic insulation composites from recycled cellulose-based fibers and silica aerogel. The resultant cellulose-aerogel composites exhibit thermal conductivity of 34.68 mW m −1 K −1, mechanical flexibility with a flexural modulus of 429.21 MPa, and superhydrophobicity with water contact angle of 158.72°. Moreover, we present the additive manufacturing process of recycled cellulose aerogel composites, providing enormous potential for high energy efficiency and carbon-sequestration building applications.